2021
DOI: 10.1038/s41598-021-92582-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of brain-wide somatosensory BOLD fMRI in mice under dexmedetomidine/isoflurane and ketamine/xylazine

Abstract: Mouse fMRI under anesthesia has become increasingly popular due to improvement in obtaining brain-wide BOLD response. Medetomidine with isoflurane has become well-accepted for resting-state fMRI, but whether this combination allows for stable, expected, and robust brain-wide evoked response in mice has yet to be validated. We thus utilized intravenous infusion of dexmedetomidine with inhaled isoflurane and intravenous infusion of ketamine/xylazine to elucidate whether stable mouse physiology and BOLD response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(57 citation statements)
references
References 70 publications
4
51
0
Order By: Relevance
“…To verify our simulation results with in vivo studies, we performed ofMRI in Thy1-ChR2 mice under light anesthesia with three different irradiance levels on nine different atlas-based cortical regions: unilateral motor (primary, MOp; secondary, MOs) areas, primary somatosensory (barrel field, SSp-bfd; upper and lower limb, SSp-ul/ll) areas, visual (primary, VISp; anterior and rostrolateral, VISa/rl) areas, auditory (AUD) areas, medial (antero- and posteromedial visual, VISam/pm) areas and bilateral retrosplenial areas (dorsal and ventral, RSPd/v) 30 ( Fig. 3f-m ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To verify our simulation results with in vivo studies, we performed ofMRI in Thy1-ChR2 mice under light anesthesia with three different irradiance levels on nine different atlas-based cortical regions: unilateral motor (primary, MOp; secondary, MOs) areas, primary somatosensory (barrel field, SSp-bfd; upper and lower limb, SSp-ul/ll) areas, visual (primary, VISp; anterior and rostrolateral, VISa/rl) areas, auditory (AUD) areas, medial (antero- and posteromedial visual, VISam/pm) areas and bilateral retrosplenial areas (dorsal and ventral, RSPd/v) 30 ( Fig. 3f-m ).…”
Section: Resultsmentioning
confidence: 99%
“…For MRI experimental preparation, mice were initially kept in a chamber with 4% ISO for ~4 min for anesthesia induction. In the case of ketamine/xylazine anesthesia 5 , a ketamine (100 mg/kg) and xylazine (10 mg/kg) mixture was first injected intraperitoneally (IP) and maintained by intravenous (IV) continuous infusion of ketamine (35-45 mg/kg/hr) and xylazine (1.75-2.25 mg/kg/hr) into the tail vein during experiments. For the ISO experimental group, 1% ISO was maintained throughout the preparation and experiment.…”
Section: Methodsmentioning
confidence: 99%
“…These results indicate that low-dose anesthesia can be useful to investigate the abnormality of the functional network in resting state, although the limitation of interpretation of fMRI under light anesthesia still exists. Despite common functional connectivity between awaked and lightly anesthetized state ( Grandjean et al, 2020 ; Tsurugizawa and Yoshimaru, 2021 ), fMRI signal changes to the physiological stimuli are significantly disturbed by the anesthetic ( Peeters et al, 2001 ; Tsurugizawa et al, 2010 , 2016 ; Aksenov et al, 2015 ; Tokunaga et al, 2021 ; You et al, 2021 ). As an alternative, awake mouse fMRI is developed using habituation training to reduce stress during MRI experiments ( Tsurugizawa et al, 2013 , 2020 , 2021 ; Bergmann et al, 2016 ; Yoshida et al, 2016 ; Madularu et al, 2017 ; Chen et al, 2020 ; Russo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, anesthesia drug- and dose-dependently modulated the neural activity triggering changes in BOLD signal intensity. Many studies suggested the dexmedetomidine plus low-dose isoflurane anesthesia was conducted on the rodent to result in the boxcar-like BOLD response with consistent hemodynamic patterns in the contralateral sensorimotor cortical regions induced by the somatosensory stimulation 51 53 . In this study, the mice were anesthetized with 0.03 mg/kg dexmedetomidine hydrochloride subcutaneously after induction with 3% isoflurane (Attane, Minrad Inc., Bethlehem, PA, USA) mixed with 20% O 2 , 75% N 2 , and 5% CO 2 for 5 min for sedation under anesthesia.…”
Section: Methodsmentioning
confidence: 99%
“…A biphasic electrical current with a pulse width of 0.2 ms was delivered and applied by using an isolated stimulator (S48, Grass Technologies, West Warwick, RI, USA) with an isolated constant-current unit (PSIU6, Grass Technologies, West Warwick, RI, USA). The intensity and frequency of the electrical stimulation were 1 mA and 12 Hz, respectively, as commonly used to evoke the contralateral sensorimotor cortical BOLD activation in dexmedetomidine sedated rodents 53 , 54 .…”
Section: Methodsmentioning
confidence: 99%